Influence Of Smartphone Attributes On Student’s Buying Decision In Lagos State Tetiary Institutions - Patrick Kunle A Ladipo; Mufutau Akanbi Awoniyi; Olushola Solomon Akeke (University of Merdeka Malang, 2018)
The study was carried out to evaluate the influence of smartphone attributes on student’s buying decision in Lagos State Tertiary Institutions. Research design adopted was purely descriptive, employing cross sectional survey method in data collection. Data for the study were generated through the use of structured questionnaire and administered to a sample of 362 out of 3,792 students in selected tertiary institutions in Lagos State. Data collected were analyzed using Multiple Regression Analysis. The results showed that all smartphone attributes considered in the study were found to be positively and significantly related to student’s buying decision. Specifically, technology attribute has highest impact on student’s buying decisions, followed by application and price attributes. The study concluded that technology, application and price are considered the most top three attributes that significantly influenced student’s buying decision of Smartphone. It was recommended that firms should focus on improving their technology in other to bring about innovative features and application, and more importantly adopt variety of price strategies while not neglecting the image and design attributes, as these were regarded as secondary attributes in determining consumers’ choice of Smartphone. https://doi.org/10.26905/jmdk.v6i1.1938